2020
DOI: 10.1101/2020.09.10.289561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nicotinamide mononucleotide (NMN) deamidation by host-microbiome interactions

Abstract: Treatment with nicotinamide mononucleotide (NMN) is a prominent strategy to address the age-related decline in nicotinamide adenine dinucleotide (NAD+) levels for maintaining aspects of late-life health. It is assumed that exogenous NMN is directly incorporated into NAD+ in mammals by the canonical recycling pathway, however the need for NAD+ is conserved across evolution, including bacteria in the gut microbiome, which can deamidate NMN to nicotinic acid mononucleotide (NaMN). Here, we use strategic isotope l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 81 publications
1
6
0
Order By: Relevance
“…Thus, translation of our in vitro data into in vivo predictions depends on these unknown levels but the ranges we studied are close to those relevant to some physiological and pathological states. For instance, our previous study ( Mori et al., 2014 ) was our reference for basal axonal NAD and NMN levels, in close agreement with others ( Cuny et al., 2021 ; Di Stefano et al., 2017 ; Kim et al., 2020 ; Parker et al., 2020 ) and we also showed that NMN rises and NAD falls in damaged nerves ( Di Stefano et al., 2015 ). Also presently unknown are the contribution (if any) from glia to pyridine metabolism in neuronal cells, and any modulating effects of SARM1 interacting proteins.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, translation of our in vitro data into in vivo predictions depends on these unknown levels but the ranges we studied are close to those relevant to some physiological and pathological states. For instance, our previous study ( Mori et al., 2014 ) was our reference for basal axonal NAD and NMN levels, in close agreement with others ( Cuny et al., 2021 ; Di Stefano et al., 2017 ; Kim et al., 2020 ; Parker et al., 2020 ) and we also showed that NMN rises and NAD falls in damaged nerves ( Di Stefano et al., 2015 ). Also presently unknown are the contribution (if any) from glia to pyridine metabolism in neuronal cells, and any modulating effects of SARM1 interacting proteins.…”
Section: Discussionsupporting
confidence: 92%
“…Although there are no patients with Congenital NAD Deficiency Disorder currently recorded on niacin supplementation, given the established benefit of supplementation in adults (Rajman et al, 2018), and the potential to benefit the speech and developmental delays associated with HAAO LOF patients (Shi et al, 2017), it will be interesting to follow the progression of this patient over time. Therapeutic administration of the NAD precursors nicotinamide riboside (Trammell et al, 2016) and nicotinamide mononucleotide (Kim et al, 2020) have been shown to significantly bolster NAD synthesis via the de novo pathway via direct or indirect means, respectively, while nicotinamide riboside supplementation in humans has been documented with minimal adverse physiological outcomes (Trammell et al, 2016). The choice between NAD precursors for future therapeutic recommendation is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Production of NAD and NA from NR can occur multiple ways, e.g., (i) NR to NAD to NAM to NA; (ii) NR to NAM to NA to NAD; (iii) NR to nicotinic acid riboside (NAR) to NAD and/or NA. Given that NR has been reported to be more effective than equivalent doses of NAM or NA 48 and that metabolism of oral nicotinamide mononucleotide was recently suggested to proceed via the deamidated mononucleotide 49 , we were particularly intrigued by possibility (iii).…”
Section: Nicotinamide Riboside Boosts Tissue Nad Pools Via Breakdown and Deamidation To Nicotinic Acidmentioning
confidence: 99%